2014
DOI: 10.1371/journal.pone.0093102
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Insight into Mutational Landscape of Head and Neck Squamous Cell Carcinoma

Abstract: Development of head and neck squamous cell carcinoma (HNSCC) is characterized by accumulation of mutations in several oncogenes and tumor suppressor genes. We have formerly described the mutation pattern of HNSCC and described NOTCH signaling pathway alterations. Given the complexity of the HNSCC, here we extend the previous study to understand the overall HNSCC mutation context and to discover additional genetic alterations. We performed high depth targeted exon sequencing of 51 highly actionable cancer-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 85 publications
1
52
0
1
Order By: Relevance
“…HPV integration in the UM-SCC-047 cell line was located in close proximity (5.5Mb) to the fragile FRA3C site, which is known to have a high double-stranded break rate (10, 11). Additionally, sites of HPV integration were near known cancer-related genes in our samples: TP63 (18) (047 cell line); FOXE1 (53) (090 cell line); NOTCH1 (8) (PDX2); and EGFL7 (54) (PDX2). This suggests that HPV integration occurs near genes that play a central role in HNSCC development (Tables S3–S6).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…HPV integration in the UM-SCC-047 cell line was located in close proximity (5.5Mb) to the fragile FRA3C site, which is known to have a high double-stranded break rate (10, 11). Additionally, sites of HPV integration were near known cancer-related genes in our samples: TP63 (18) (047 cell line); FOXE1 (53) (090 cell line); NOTCH1 (8) (PDX2); and EGFL7 (54) (PDX2). This suggests that HPV integration occurs near genes that play a central role in HNSCC development (Tables S3–S6).…”
Section: Discussionmentioning
confidence: 88%
“…Several high-throughput genomic analyses, aimed at facilitating the development of cancer-related therapy, revealed that HPV+ tumors have fewer genetic alterations than non-HPV-related HNSCCs (3, 8). The virus-related dysfunction of the APOBEC complex in HPV+ HNSCC (9) leads to accumulation of the non-synonymous mutations within the isolated hot-spots, resulting in genetically-homogeneous disease and narrowing down the number of potential targeting candidates.…”
Section: Introductionmentioning
confidence: 99%
“…With several highly cited genomic studies in head and neck tumors and a soon to be released TCGA study, it is clear that there is an opportunity to identify mutation, copy number and differential gene expression in these tumors to better inform treatment and prognosis than by HPV status alone [27][28][29][48][49][50][51]. The mutational spectrum shown in the HPV-negative tumors of this small study demonstrated a high mutational burden in these tumors and a source of potential difficulty in interpreting and reporting using exome or many ([100) gene diagnostic panels which could yield hundreds or thousands of variant calls.…”
Section: Discussionmentioning
confidence: 99%
“…A targeted NGS panel (the VC NGS panel) was designed using previously published data on somatic mutations in VC, its precursors (12), and in HNC (13,14,(19)(20)(21). The panel consists of 176 amplicons covering 97% of the coding region of 17 genes with a role in critical cellular pathways, such as differentiation, proliferation, and apoptosis .…”
Section: Development Of the Targeted Vulvar Ngs Panelmentioning
confidence: 99%